A two-year dataset of energy, environment, and system operations for an ultra-low energy office building - Jung Min Han; Ali Malkawi; Xu Han; Sunghwan Lim; Elence Xinzhu Chen; Sang Won Kang; Yiwei Lyu; Peter Howard (Scientific Data, 2024)
Abstract This paper describes a two-year high-fidelity dataset for an ultra-low energy office building and living laboratory called HouseZero ®. The building integrates multiple low-energy technologies, such as natural ventilation with automatic windows, ground source heat pump, and thermally activated building systems. The building’s performance is continuously monitored with an extensive sensor network. The dataset consists of breakdown energy end uses, photovoltaic (PV) production, zone-level indoor environment including indoor air temperature, CO2 concentration, and relative humidity, micro-climatical conditions, building façade temperature, and detailed system operations including zone-level BTU meter, valve status, slab temperature, window/skylight opening status, heat pump, and geothermal well operations. The data can be used to support data analytics of ultra-low-energy building operations, and data-driven modeling of low-energy building systems.